Can the effects of the mitochondrial DNA mutations found in Leber's hereditary optic neuropathy be protective against the development of cluster headache in smokers? - Todd D Rozen (SAGE Publishing, 2020)
Is it possible that some mitochondrial DNA (mtDNA) mutations enhance the risk of developing a headache disorder while other mutations actually confer a protective effect? Mitochondrial disorders have been linked to migraine but very rarely to cluster headache (CH). The true pathogenesis of CH is unknown but a linkage to cigarette smoking is irrefutable. Leber's hereditary optic neuropathy is a syndrome of bilateral vision loss that typically manifests in a patient's 20s and 30s, is male predominant, and its sufferers are heavy smokers and heavy drinkers. Tobacco exposure is so linked to the condition that only smokers appear to develop vision loss while nonsmokers remain unaffected carriers of their mutations. In essence, the Leber's hereditary optic neuropathy population is the CH population but at present there have been no reported cases of CH in this mitochondrial subgroup. Thus, could the effects of the mtDNA mutations found in Leber's hereditary optic neuropathy, which involve complex I of the electron transport chain, actually confer a protective effect against the development of CH? This article will delve into this theory.